Evaluating the life cycle CO2 emissions and costs of thermoelectric generators for passenger automobiles: a scenario analysis. (10th July 2016) - Kishita, Yusuke; Ohishi, Yuji; Uwasu, Michinori; Kuroda, Masashi; Takeda, Hiroyuki; Hara, Keishiro
Abstract: A thermoelectric generator (TEG) is a device used for energy harvesting that enables electricity generation from waste heat. Among the various types of energy harvesting technologies developed for achieving a low-carbon society, the TEG is characterized by its ability to recover energy from heat sources with temperatures as low as 200–300 °C. However, for economic and technological reasons, the TEG market has not yet been developed. With the goal of clarifying the performance required in order for TEGs to be practical and widely available in society, this paper analyzes several life cycle scenarios from both environmental and economic viewpoints. We herein focus on passenger automobiles, because the temperature of their exhaust gas is suitable for TEGs. A case study is carried out in which TEGs are installed in passenger automobiles in Suita City, Osaka, Japan. By applying a scenario planning method, we describe four scenarios that differ according to the technological performance of the TEGs and the driving pattern, under which the life cycle CO2 emissions (LCCO2 ) and costs of each scenario are evaluated. Comparison of the four scenarios reveals that improving the thermoelectric figure-of-merit by a factor of 1.9 is necessary in order to reduce the LCCO2 to zero while assuming the average driving pattern in Suita City. In addition, in order to make TEGs profitable over their life cycle, the price of TEGs must be reduced to approximately 10–40% of their current price.